2008
DOI: 10.1093/jn/138.9.1658
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Calcium and Cholecalciferol Modulate Cyclin D1 Expression, Apoptosis, and Tumorigenesis in Intestine of adenomatous polyposis coli1638N/+ Mice1,

Abstract: Both epidemiological and experimental findings have indicated that components of Western diets influence colonic tumorigenesis. Among dietary constituents, calcium and cholecalciferol have emerged as promising chemopreventive agents. We have demonstrated that a Western-style diet (WD) with low levels of calcium and cholecalciferol and high levels of (n-6) PUFA, increased the incidence of neoplasia in mouse intestine compared with a standard AIN-76A diet; models included wild-type mice and mice with targeted mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 32 publications
0
34
0
1
Order By: Relevance
“…Some animal studies indicated that vitamin D status may influence the growth of intestinal tumors (76)(77)(78)(79). Vitamin D status modulates various genes in the colorectal mucosa that may influence the cancer risk (71,80).…”
Section: Discussionmentioning
confidence: 99%
“…Some animal studies indicated that vitamin D status may influence the growth of intestinal tumors (76)(77)(78)(79). Vitamin D status modulates various genes in the colorectal mucosa that may influence the cancer risk (71,80).…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and animal studies show that calcium (11)(12)(13) and vitamin D (14) exert an impact on pathways involved in colonic neoplasia. However, these studies do not determine the direct effects of these compounds on the colon of subjects at risk of developing CRC.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The mechanism by which this chemoprevention occurs is not understood. 4 Although increased dietary calcium could chelate and reduce bile acid concentration in the lumen, a different target of increased luminal calcium is the extracellular calcium-sensing receptor or CaSR.…”
mentioning
confidence: 99%